Pemilihan Sekolah Swasta Berbasis Agama dalam Perspektif Angst Society - Nurhadi, Nurhadi (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2018)
There has been a sharp increase of the number of parents sending their children to religious-based private schools, ranging from early childhood education to that of high school, since the past three decades. In addition to the urban and peri-urban population, this trend has also been extending that of rural, in which individual decision making is presumed to be also strongly influenced by, or at least takes account seriously consideration made by, extended family. This research focuses on how parents come up with the decision to send their children to religious-based private school. Applying social network analysis, this research aims at understanding and explaining the process of socialization, dissemination, and the fortification of ideas on the importance of sending children to the religious-based private school. The results of this research are: First, there is the certain dominant perception among parents that the community and society at-large in which parents and their families belong to pose threats to the growth of children and teenagers. Second, there are certain negative perceptions on public and non-religious-based schools. The teaching of religious, moral, and virtuous values are considered as insufficient.